PENGARUH TERAPI BEKAM TERHADAP KADAR ASAM URAT PADA PASIEN DI KLINIK SEHAT DR. ABDURRAHMAN MEDAN TAHUN 2020 - SYIFA SYAHIRAH; EKA AIRLANGGA (JURNAL ILMIAH KOHESI, 2021)
Cupping therapy is one alternative treatment that is widely used by the public. Cupping Therapy is a method of treatment byremoving blood contaminated with toxins or oxidants from the body through the skin surface. Cupping is believed to havebenefits for treating various diseases and can reduce uric acid levels. However, there are also several studies that statecupping therapy does not have a significant effect on uric acid levels. This must be accompanied by research to concludescientific facts about cupping. To determine the effect of cupping therapy on uric acid levels conducted at the Health Clinicdr. Abdurrahman Medan in 2020. This type of research is analytic descriptive with cross sectional design by comparing thepre-test and post-test scores in one group without comparison. Sample size were 44 people who met the inclusion andexclusion criteria determined by purposive sampling. Analysis of the data used is the paired T-test. The results analysis ofpaired T test showed that there was an effect of cupping therapy on uric acid levels with a value of p = 0.000(<0.05).Cupping therapy can reduce uric acid levels.